Penghitungan Kemiskinan Di Kalimantan Selatan Menggunakan Pendekatan Paritas Daya Beli - Ahmadi Murjani (Puslatbang KHAN, 2018)
The rigorous and sustainable monitoring and evaluating the poverty rates are inevitable in measuring the efficacy of a nation’s development. The poverty rate itself depends on many influential variables, one of which is the poverty threshold/line. Concerning its high impact on the poverty rate produced, it is essential to assess the poverty line measurement in order to yield a valid and robust poverty rate. This paper aims to investigate the poverty lines in Indonesia especially in South Kalimantan utilizing the Purchasing Power Parity approach. In the situation of a shortage of poverty line comparison literature, this paper tries to fill such gap. This paper utilizes data from the World Bank (The World Development Indicators and The International Comparison Program) and Statistics Indonesia’s website. This paper obtains some findings; in a particular time, the South Kalimantan’s poverty line was above the World Bank 1.90-a-day standard. However, most of the times, such domestic poverty lines were below the comparator. Therefore, this paper exists not only to contribute to enriching the previous literature but also presents the other perspective to improve the construction of the domestic poverty line.